2014
DOI: 10.1016/j.ijscr.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic repair of posttraumatic diaphragmatic rupture. Report of three cases

Abstract: INTRODUCTIONPosttraumatic diaphragmatic rupture (PTDR) is a rare complication of thoracoabdominal injuries. In the emergency phase, it is generally treated via wide laparotomy. The laparoscopic approach is controversial and it is reserved for the chronic type of PTDR. Herein we present three cases of laparoscopic treatment of PTDR, one of which was conducted early after the injury.PRESENTATION OF CASEThe patients’ age was 42, 66 and 53 years and the time from the injury until the operation 1 week, 2 months and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Though penetrating and blunt trauma to the abdomen can both result in diaphragmatic rupture, penetrating abdominal trauma is the leading cause, accounting for 75% of cases [ 3 ]. The majority of ruptures occur through the left hemidiaphragm (88–95%), as opposed to the right, because of the protective effect of the liver [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though penetrating and blunt trauma to the abdomen can both result in diaphragmatic rupture, penetrating abdominal trauma is the leading cause, accounting for 75% of cases [ 3 ]. The majority of ruptures occur through the left hemidiaphragm (88–95%), as opposed to the right, because of the protective effect of the liver [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis, however, can be difficult because the physical examination may be unremarkable, and 30–50% of diaphragmatic ruptures are missed on initial imaging [ 3 ]. Failure to promptly recognize diaphragmatic rupture, with subsequent herniation, can result in delayed symptoms, sometimes months and even years later, with potential catastrophic outcomes [ 5 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic correction of diaphragmatic rupture in clinical settings has been reported by many authors and it is always associated with shorter hospital stay, faster return to normal activities and minimal postoperative complications [4][5][6][7][8][9][10][11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several authors have reported the early recovery and low incidence of postoperative complications in patients submitted to this minimally invasive approach [4][5][6][7][8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Surgical repair is necessary even for small defects, as the diaphragm will not spontaneously repair, and the variation in thoracic to abdominal pressures favors herniation of abdominal contents and expansion of the defect. Repair is typically performed through open laparotomy using interrupted non-absorbable sutures, but cases have been reported of laparoscopic repair [6].…”
Section: Introductionmentioning
confidence: 99%